Evaluación de la factibilidad de la implementación de turbinas para micro generación de energía eléctrica en conjunto con bombas de bobina (2017)
for electrification projects in rural areas where access to electricity is limited. In recent decades, small-scale power generation has become a cost-effective, clean and reliable way to generate mechanical and electrical energy. Although micro-electricity brings great advantages, it represents a challenge. For the implementation of this type of projects, specific requirements and characteristics are required at the application site. It means that each one needs to be designed so that it fits for the existing needs and conditions. Although some attempts have been made to create systems that point to decrease the dependence on specific conditions, technical expertise is still required to ensure long-term project success. It is evident that it is still necessary to work together between technical staff, management staff and the community to carry out the installation of this type of projects. According to a report from the Colombian Mining and Energy Planning Unit (UPME)...